HUMAN RESOURCES EMPOWERMENT AND CORRUPTION ERADICATION IN PUBLIC SECTORS: A BRIEF PICTURE FROM INDONESIA1 - Rohman, Abdul (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2012)
Corruption has been hampering development process in Indonesia and it is believed that E-government hypothetically will diminish corruption in the country. The paper briefly compares Corruption Perception Index and Egovernment Index to portray the respective case, and proposes human resources empowerment as essential tactic to curb corruption in public sectors. It concludes that E-government might decrease corruption if it is incorporated with increasing infrastructure and human capital, and; in doing so, managing human resources to exercise their individual moral identity within organization is suggested so that corruption eradication can be initiated from individual selfawareness which then evolves to collective awareness to create a common culture in corruption prevention.